Pengaruh Persepsi Harga, Kualitas Produk, dan Citra Merek Terhadap Keputusan Pembelian Motor Honda Di Dealer Kharisma - Ella Ramadhan Ningsih; Leonardo Indra Vitaharsa (Human Capital Development, 2022)
This study aims to determine the effect of price perception, product quality, and brand image on purchasing decisions for Honda motorcycles at Kharisma Dealers. The population in this study consisted of consumers who bought Honda motorcycles through Kharisma Dealers. For the number of samples used in this study, 130 respondents were selected using an accidental sampling approach and questionnaires were given to respondents. In addition, 30 respondents were intended for validity testing, and the rest were designed for research calculations. The data analysis method used in this research is multiple linear regression analysis. The analysis carried out includes validity and reliability tests, classical assumption test, multiple regression analysis, T test and F test, and analysis of the coefficient of determination (R2). The results of this study indicate that the perception of price, product quality, and brand image partially or simultaneously influence the purchase decision of Honda motorcycles at Kharisma Dealers. Keywords: Price perception, Product Quality, Brand Image and Purchase Decision